Transforming Public Sector Auditing from Tradition to Agility with Scrum: A Case for the Indonesian Public Sector - Triasmoro, Benidiktus Bambang; Mahatma, Kodrat; Budiardjo, Eko K. (Jurnal Locus Penelitian dan Pengabdian, 2025)
The conventional audit methodology in the public sector faces escalating challenges in addressing the increasing complexity of governmental functions and the demand for prompt, relevant audit results. This study addresses the critical research problem of enhancing audit efficiency and stakeholder engagement in public sector auditing while maintaining professional standards and regulatory compliance. The research objective is to develop a novel framework for implementing Agile methodology, specifically Scrum, in BPK’s public sector audit process. The study employs a qualitative research methodology, including a comprehensive literature review, document analysis, interviews with thirteen key stakeholders—comprising senior auditors and Agile practitioners—and a limited pilot implementation. The research identifies eight critical areas for framework development and establishes Quality Control Integration Points (QCIP) to ensure continuous quality monitoring while preserving agile flexibility. The findings demonstrate that Agile principles can be successfully adapted to public sector auditing through a modified Scrum framework that incorporates iterative planning, daily coordination, and consistent stakeholder feedback. The study provides a structured implementation roadmap spanning 3 to 18 months and addresses varying levels of stakeholder impact. The developed framework enhances audit efficiency and effectiveness while upholding essential compliance standards. This research contributes both to the theoretical understanding and practical application of Agile methodology in public sector auditing, establishing a foundation for future adoption in similar institutions.